La poesía-crónica de Mario Vargas Llosa: Un análisis de los poemas “Padre Homero” y “Estatua viva” - Loayza Maturrano, Edward Faustino (2025)
This study delves into the chronicle-poetry of Mario Vargas Llosa, focusing on the poems “Padre Homero” and “Estatua viva.” Despite the rich complexity of his narrative, there is a gap in understanding how his poeticized chronicles serve as a confluence of urban echoes and popular characteristics, promoting the appropriation of both near and distant contexts. This research seeks to elucidate this intersection through the analysis of the mentioned poems using a qualitative methodology of discourse analysis. The analysis highlights the polysemy of everyday perception and identity memory in these texts, positioning Vargas Llosa as a keen observer who enriches his symbolic capital by integrating everyday knowledge into his literary canvas. The findings underscore the function of the poems as social practice, reflecting the formal and social properties of language. The study identifies an unstable discursivity in the poems, where literary language intersects with other social discourses, such as journalism and visual arts. This is exemplified by the integration of images from the works of Peruvian painter Fernando de Szyszlo, further blurring the boundaries between poetry and visual arts. It concludes that Vargas Llosa’s chronicle-poetry serves as testimony to the power of literary chronicles to capture the dialectical space between narrative and reality. These poems not only enrich the reader’s understanding of social literature but also suggest future lines of research exploring the integration of visual and literary arts.